National identity and interethnic tolerance: A study from Croatia - Čorkalo, Dinka (Array, 2000)
National identity is an issue, which occupies the interest of researchers in many fields: sociology, political science, philosophy, history, anthropology and so on. Despite its undoubted importance, the question of national identity has been relatively rarely examined by psychologists. History, especially recently, speaks for itself about the importance of a nation and peoples attachment to it. After the collapse of the communist system in all Eastern European countries the question of national identity and processes of national homogenization have become stronger and very important. Understanding the phenomenon of national identity is not only a question from a theoretical point of view, but has an extremely practical value as well. That is, the study of national identity has a practical value as a means of identifying possible directions for encouraging interethnic tolerance. This is particularly important if we bear in mind the fact that there are relatively few nationally homogenous countries and that the consequence of globalization is multiethnicity and multiculturalism. Research on national identity in psychology, which has been done thus far, could be questioned for several reasons. Firstly, the amount of theoretical work surpasses empirical research and one can direct serious objections to the latter: most of the studies have been conducted with children or non-representative samples, both of which restrict our ability to generalize the obtained results. Secondly, the social context of intergroup relations is often neglected in psychological work. Furthermore, research has been conducted with minority groups. Since different scholars use very different definitions and measures, it is hard if not impossible to compare obtained data. In studying national identity one should ask several important questions: what are the components of national identity? How could we measure them? How are they expressed? We propose National Identity Scale (Corkalo and Kamenov, 1999) as a measure of national identity defined as an attachment to ones nation (ethnicity) and the sense of belonging to it. The results of research on national identity conducted in Croatia in 1998 and 2000 will be presented as well as their relations to measures of interethnic tolerance.